Agis IV, Kleomenes III, and Spartan Landscapes 1 - D Graham J Shipley (Historia, 2017)
Possible attempts, by state or individuals, to combat inequality by cultivating unused land or ignoring the prohibition on manual labour did not solve the problem. Since Sparta and perioikic poleis possessed distinct territories, 'Malea(s)' in Plutarch's account of Agis's land reforms should mean Mt Parnon, not Cape Malea; it was only Sparta's own chora that Agis IV and Kleomenes III could redesign. Modern studies of the two men's careers have often focused on such topics as military strategy, Kleomenes' manipulation of Spartan education, and the reliability of Plutarch and his sources,3 notably the non-Spartan Phylarchos, a sympathetic eye-witness to the events of Kleomenes' reign.4 A fuller understanding can be gained if we start from the principle that in order to understand the history of a polis we must try to comprehend both its internal dynamics and its external links. A precise analysis of Sparta's manpower problem and its likely impact on the landscape (§§ 2-4), a reassessment of key topographic and numerical evidence (§§ 5-8), and a clear formulation of likely changes in Sparta's relationship with other communities (§§ 9-11) will clarify the intentions of the kings and the restrictions under which they were operating. 2.Sparta's Manpower Problem The Spartan economy in the classical period depended heavily upon agricultural produce delivered to the citizens from conquered lands in Messenia, farmed by helots. Evidently the Spartan authorities were not so short-sighted as to deprive the polis of the services of hundreds of trained fighters; and it may be that Inferiors, though...